Sistem Informasi Pengelolaan Pajak Kendaraan Bermotor Berbasis Web Pada Dinas Pendidikan dan Kebudayaan Kabupaten Tabalong - Ilmi, Bahrul; Naury, Chairullah; Harmaji, Lilik (Politeknik Harapan Bangsa Surakarta, 2025)
Web-Based Motor Vehicle Tax Management Information System at the Tabalong Regency Education and Culture Office. The Web-Based Motor Vehicle Tax Management Information System at the Tabalong Regency Education and Culture Office is a web-based application aimed at assisting in the management and payment of motor vehicle taxes within the Tabalong Regency Education and Culture Office environment. At the Tabalong Regency Education and Culture Office, there are frequent delays in vehicle tax payments by school principals, with reasons such as forgetting to check the tax due date and difficulties in obtaining referral letters from the office. This research aims to build a web-based motor vehicle tax management information system that enables real-time and transparent monitoring and reporting of the office's vehicle tax payment status, as well as assisting school principals in monitoring tax payment due dates and simplifying the process of obtaining referral letters at the Tabalong Regency Education and Culture Office. The system development method used is the waterfall method, with problem limitations on the management of office vehicle taxes within the scope of the Tabalong Regency Education and Culture Office, and a focus on information regarding tax validity periods, tax payment status, and the creation of tax referral letters. This information system is built using the Laravel 10 framework. With the presence of this information system, it is expected to assist the Tabalong Regency Education and Culture Office in managing official vehicle taxes in a more efficient, accurate, and transparent manner.